Female genital tuberculosis: a clinical lecture - Ekaterina V. Kulchavenya (IP Berlin A.V., 2022)
The problem of extrapulmonary tuberculosis (EPT) remains urgent since, along with a decrease in the incidence of the disease, there is an increase in the number of neglected, late diagnosed cases. Female genital tuberculosis (FGT) is a relatively rare disease difficult to diagnose, occurring on average in 0.52.0 cases per 100,000 population; in recent years, an increase of EPT in this localization has been observed. Tuberculosis can affect any organ of the female genital system, either single or in combination. The most frequently involved are the tubes (95100%), endometrium (5060%), ovaries (2030%), cervix (515%), myometrium (2.5%) and vagina/vulva (1%). The most common symptom of FGT that makes patients seek medical advice is infertility. Other symptoms of FGT include menstrual irregularities (oligo-, hypo-, dis-, amenorrhoea as well as meno- and metrorrhagia), pelvic pain, and abnormal vaginal discharge. In postmenopausal women, FGT is characterized by symptoms resembling endometrial malignancy, such as postmenopausal bleeding, persistent leukorrhea, and pyometra. The diagnosis is based on a thorough history, clinical examination, and proper examination of the sample material obtained by endoscopy. Tuberculin test with intradermal injection of 2 TU of tuberculin (Mantoux test) was positive in 42.6% of patients with genital tuberculosis. Hysterosalpingography is an important method for diagnosing FGT, which assesses the internal structure of the female reproductive tract and the patency of the fallopian tubes. On ultrasound, the fallopian tubes may appear dilated, thickened, or filled with serous discharge (hydrosalpinx) or caseous mass (pyosalpinx). Laparoscopy and dye hydrotubation are reliable tools for the diagnosis of genital tuberculosis, especially for the involvement of the fallopian tubes, ovaries, and peritoneum. Microbiological examination of sampled material in FGT using solid media is low-informative; polymerase chain reaction and other molecular diagnostic methods should be used. It should be acknowledged that FGT is not a rare condition, but it is often overlooked. The two main reasons for late diagnosis are vague clinical signs and low alertness. Since infertility is a frequent complication of FGT, all infertile women should be screened for tuberculosis: tuberculin, ultrasound, hysterosalpingography, and in complicated cases, diagnostic laparoscopy with obligatory tissue sampling for pathomorphological and microbiological studies.